Showing, Telling and Seeing. Metaphor and “Poetic” Language - Elisabeth Camp (Baltic International Yearbook of Cognition, Logic and Communication, 2007)
Theorists often associate certain “poetic” qualities with metaphor – most especially, producing an open-ended, holistic perspective which is evocative, imagistic and affectively-laden. I argue that, on the one hand, non-cognitivists are wrong to claim that metaphors only produce such perspectives: like ordinary literal speech, they also serve to undertake claims and other speech acts with propositional content. On the other hand, contextualists are wrong to assimilate metaphor to literal loose talk: metaphors depend on using one thing as a perspective for thinking about something else. I bring out the distinctive way that metaphor works by contrasting it with two other poetic uses of language, juxtapositions and “telling details,” that do fit the accounts of metaphor offered by non-cognitivists and contextualists, respectively.
Keywords: philosophy; linguistic